Pragmatic of the title in the great literature of Ibn Al-Muqaffa - Taheri , Ali; Zadeh, Masuma (Al-Adab Journal, 2025)
The book The Great Writer is one of the most prominent books written by Ibn al-Muqaffa, and it played a major role in defining the Arab world and raising its artistic and rhetorical level among writers. Given the artistic, historical, literary and scientific value it contains, we decided to shed light on the book Let us discover the most important functions of the title based on the pragmatic approach. The research concluded with several results, namely that the book was distinguished by several aspects according to the perspective of pragmatics, especially in the functions of the titles, as the titles in the book of great literature had multiple important meanings that revolved around many social and political issues, and they carry two types of meaning, which is the descriptive function and the seductive function. The descriptive function was to shift the role of titles dealing with politics, so it revolved around dealing with the Sultan and the necessity of guarding against him, the way to deal with him, introducing his character and what the Sultan likes towards his subjects, taking care of the affairs of the elders rather than the minors, the types of kingship, delegating matters to the competent, inspecting the subjects, etc The Sultan requires it from The matter of the world. The seductive function was often evident in the writer’s speech for people to deal with their world and the ruler and the principles that they must follow, which were represented in: keeping company with the ruler with caution, not questioning the Sultan, warning against the ruler’s wrath, being kind to the Sultan’s entourage and his group, tolerating disagreement, correct advice to the Sultan obedience to kings, Behave with knowledge, be humble, and avoid lying and slander.